Kurumsal Kimlik Tasarımı Bağlamında Web Tasarımının Dijitalleşme Sürecinde Kimlik Sorunsalı Ve Sürdürülebilirlilik - SATIR, DİDE AKDAĞ (The Turkish Online Journal of Design, Art and Communication, 2012)
The visual element of the Internet, which can distribute message to the mass, web design, at the end of the interaction it created on the receptive mass should be suitable to the aim and the style of the institution. Web designer and programmer should produce designs and software unique to the identity of the institution. Web sites that are ready made are far from being authentic and professional. Web sites are prepared in accordance with to the visual satisfaction to the institution that demands it, rather than the inclination of the clients or the visitors using them. This is an extremely wrong attitude. A professional web site should be prepared according to its aim. It should be functional, shouldn’t include unnecessary and improper items. An effective web design interface can be recognized clearly and consistently by the target group. The sustainability of the institutional identity design in the process of digitalization can materialize by protecting the factors that form the resource and values that are unique to the design while using them. The reason of being unqualified is not being able to have a good relation between web design interface design and sustainability in the process of visual identity design. The most important supplementary that forms the web design interface, typeface will be shaped with examples on the need of using it appropriate and in place. As a sample research that different aspects of a design can be detected relational screening model has been adapted. In this study, it is aimed that a new model is submitted to digitalization, with sustainability approach and by protecting the values of web design, which is included in visual identity design that is a part of institutional identity design, as the extension of identity in the Internet environment. With the model that is aimed to be submitted steps to solve to the problems of typography concord and identity towards progression are meant to be taken. It also aims to create an integrity by making the design more qualified and with to increase sensibility by schematic and social responsibility.
Keywords: Digitalization; Web Design; Typography; Sustainability; Dijitalleşme; Web Tasarım; Tipografi; Sürdürülebilirlik